The internationalization of the cosmetic retail industry: a history of success? - Guimbert, Marie (2013)
The retailing industry has increasingly become global over the past few decades, illustrating visually the internationalization of business in general. Many retailers are betting to expand their activities internationally in order to avoid the saturation of their business in their country of origin (Alexander, 1990), increase profits or imitate competitors (Williams, 1992). Therefore, they have become considerable global players: they provide new products in the marketplace as well as being more influent within the global supply chain (Williams, 1992). Looking at the internationalization of retail more closely, the cosmetic industry provides with many examples of, what seems to be, successful achievements. The purpose of this work is to analyze the process of internationalization of four international competitors in the cosmetic retailing. Even though the field of retail internationalization has already been subject to many studies, this works aims at understanding, through the use of a multiple case study, the strategy of cosmetic retailers entering international markets. Through a qualitative study, the main question guiding this work will be to understand if every international cosmetic retailer has been following and still follows the same business and marketing strategies in order to become global. A multiple-case study was undertaken in order to compare four companies specialized in the cosmetic retail, with activities abroad. Results clearly expose differences between the internationalization processes, especially based on the companies’ nationality.